Decreasing Patience in Humans: Causes, Effects, and the Way Forward (The Harvest, 2026)
Humans, who were once able to wait for news of loved ones for a long time, are now anxious to receive information within minutes and seconds. Technology may contribute to this change in human nature, as technology and social media have become an integral part of human life. While their appropriate use can certainly be beneficial, studies and research indicate that excessive and inappropriate use has brought disadvantages to many aspects of human life. Excessive use has not only led to a kind of addiction in many people but has also unnaturally altered human behavior. Is it possible that technology and social media are causing a decline not only in human behavior but also in patience and overall human capability? The main objective of this article is to analyze the changes in human behavior and their effects caused by mobile phones and social media, and to provide suggestions on focusing on their proper use. The article is based on facts obtained from the study and review of secondary materials. Although this explanatory and analytical article has been prepared using this methodology, it does not include facts and data from primary sources. It is believed that the article will be useful for those interested in the use of mobile phones and social media and their effects.